Proximate and Mineral Composition of Meliponula beccarii Bees Honey from Potential Areas of Oromia - Kabeba, Dheressa; Meseret Gemeda; Teferi Damto (International Journal of Applied Sciences: Current and Future Research Trends, 2024)
Stingless bee honey from various areas has its own unique components because of difference in flora, climate condition, and different methods of purifying and storage condition of honey. The objective of this study was to investigate the proximate and mineral composition of M. beccarii honey from different areas including Tokke kuttaye, Chalia, Gera, Bacho, Alle and Didu districts of Oromia region in Ethiopia. Moisture, ash, protein and fat contents were determined using oven drying, muffle furnace, Kjeldahl and Soxhlet extractor methods, respectively. Mineral composition of honey was analyzed using Atomic Absorption Spectrometry method after digestion. The proximate results of moisture, ash, protein, fat, and carbohydrate were 23.20-34.88, 0.14-0.34, 0.11-1.42, 0.11-0.16 and 63.02-75.23 g/100g, respectively. Mineral composition of stingless bee honey for Na, K, Ca, Mg and P range was 59.46-490.60, 1351.60-5892.11, 67.58-426.63, 20.16- 96.57 and 0.1-0.18 mg/kg, respectively. The results have shown that this honey is a good source of carbohydrate and potassium because the contents of these macronutrients were found to be high in the honey when compared to others. This could show the honey can be branded and supplied in honey supply chains especially at supermarkets. The results of this study also indicated that the mineral contents of honey varied among the locations which might be caused by the natural absorption of minerals by plants from the soil and the environment.